Infrastructure, Resources and Services in IIT Libraries: Results of a Questionnaire Survey - Jeevan, V. K. J.; Padhi, P (Journal of Information and Knowledge, 2008)
Studies on various aspects of libraries in premier institutions, such as, IITs, IIMs, and Central Universities are of continued interest to Library and Information Science researchers. The main motivation for such studies are the inherent advantages of taking these libraries as samples as they are obviously well organized, have better services and efficient infrastructure, made a mark for themselves, and they can be comprehensively studied with ease as they are few in number. As part of MHRD-SAI project, the Central Library of Indian Institute of Technology, Kharagpur is involved with the development of a content personalization system to deliver specialized research information in a personalized mode to its faculty members. With related interests in science and technology addressed with the help of similar facilities of research and information, it entails the possibility of looking for parallels in these facilities and to extrapolate and replicate innovative services in one Institute to the others. To extrapolate the personalization prototype under development at IIT, Kharagpur to other IITs, it was decided to undertake a questionnaire survey and this paper presents the responses received to this survey about section of the questions dealing with collection, infrastructure, services, and staff of different IITs.